2015
DOI: 10.1080/17439760.2015.1015158
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability, and impact of a web-based gratitude exercise among individuals in outpatient treatment for alcohol use disorder

Abstract: This mixed-methods pilot study examined the feasibility, acceptability, and impact of a web-based gratitude exercise (the ‘Three Good Things’ exercise (TGT)) among 23 adults in outpatient treatment for alcohol use disorder (AUD). Participants were randomized to TGT or a placebo condition. The intervention was feasible with high rates of completion. Participants found TGT acceptable and welcomed the structure of daily emails; however, they found it difficult at times and discontinued TGT when the study ended. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…In previous work, participants in recovery regularly expressed gratitude for sobriety (Krentzman et al, 2015). Perhaps gratitude for sobriety functions differently in its effects on drinking than more general trait gratitude, but the scale used to measure gratitude would not have differentiated between the two.…”
Section: 0 Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous work, participants in recovery regularly expressed gratitude for sobriety (Krentzman et al, 2015). Perhaps gratitude for sobriety functions differently in its effects on drinking than more general trait gratitude, but the scale used to measure gratitude would not have differentiated between the two.…”
Section: 0 Resultsmentioning
confidence: 99%
“…Some studies have reported that gratitude exercises were associated with increases in trait gratitude (R. Emmons & McCullough, 2003; Froh, Sefick, & Emmons, 2008; Rao & Kemper, 2017; Redwine et al, 2016) while other studies have reported no change in trait gratitude as the result of gratitude practices (Harbaugh & Vasey, 2014; Killen & Macaskill, 2015; Krentzman et al, 2015; Toepfer, Cichy, & Peters, 2012). Could trait gratitude increase with the onset of addiction recovery, in the absence of gratitude exercises?…”
Section: 0 Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have begun to demonstrate the efficacy of interventions that specifically target positive affect for people living with chronic physical and mental health conditions (Boutin-Foster et al, 2016; Caponigro et al, 2013; Carrico et al, 2015; Cohn et al, 2014; Huffman et al, 2015; Huffman et al, 2011; Krentzman et al, 2015; Ogedegbe et al, 2012; Peterson et al, 2012; Seligman et al, 2005). Although most of these studies have been small pilot feasibility and preliminary efficacy studies, Charlson and colleagues have conducted larger-scale randomized trials of a positive affect intervention in samples of people with chronic illness and hypothesized that the intervention would have beneficial effects on health behaviors (Mancuso et al, 2012; Ogedegbe et al, 2012; Peterson et al, 2012).…”
mentioning
confidence: 99%